2014
DOI: 10.1136/neurintsurg-2013-010969
|View full text |Cite
|
Sign up to set email alerts
|

Lenticulostriate aneurysms: a case series and review of the literature

Abstract: LSA aneurysms are rare entities that present several treatment challenges. We have summarized the cumulative experience with these lesions and proposed a classification scheme that has treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
0
29
0
4
Order By: Relevance
“…The largest and most recent case review by Vargas et al 1 analyzed 48 reported cases of lenticulostriate perforator aneurysms. There is, however, minimal published literature on the natural history, classification, and recommended treatment of BAPAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest and most recent case review by Vargas et al 1 analyzed 48 reported cases of lenticulostriate perforator aneurysms. There is, however, minimal published literature on the natural history, classification, and recommended treatment of BAPAs.…”
Section: Discussionmentioning
confidence: 99%
“…A classification scheme for lenticulostriate aneurysms based on their relationship with the parent vessel and perforating arteries was described by Maeda et al in 200112 and re-described by Vargas et al in 2015 1. Whether classification systems alter management or outcome has yet to be determined, but they provide a means to consistently describe these aneurysms and serve as a framework for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AChA aneurysms comprise 2–5% of the intracranial aneurysms,12 13 and fewer than 60 cases of true LSA aneurysms have been reported 14 15. Owing to the small number of angiographically detected LSA aneurysms, the natural history of these aneurysms is unclear 16–18…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small size of such aneurysms, rupture results in a poor outcome, and thus treatment of incidentally detected aneurysms is reasonable 22. Most reported LSA aneurysms have been treated by craniotomy and clipping, and this certainly is an option for these lesions depending on the anatomy, with a small risk of perforator infarction (reviewed by Vargas et al 15). Catheterization and coiling of these small aneurysms carries a risk of intraoperative aneurysm rupture and of thromboembolic occlusion of the perforator arteries, especially at the neck of the aneurysm, from where these vessels usually arise.…”
Section: Discussionmentioning
confidence: 99%